Mortgage Slaves Revolt : Middle-Class Pauperization and Resistance - Rodik, Petra (2012)
During the recent financial crisis we have witnessed rapid transformation of many well-off households into debt-slaves. Impoverishment of the housing-mortgage owners led to the grassroots social movements resisting current banking policies. The most known U.S. case is far from being isolated. Worldwide, many homeowners with mortgage loans, are facing rapid pauperization, decrease of living and even health conditions, and the prospect of becoming homeless. In China, for example, a new word has recently been coined - fangnu 房奴 – “the slave of the home mortgage” – to describe young, educated people living in urban areas who pay more than 70% of their income for paying mortgage loans. I will present the results of recent research on impoverished Croatian middle class households which have mortgage loans with foreign currency clause in CHF. The results show that the impact of credit payments growth contributed greatly to the lowering of the quality of life. As many as 32% of respondents stated that over 75% of their overall monthly household income goes toward credit payment. 35% of respondents estimate the risk of mortgage repossession as high or very high. As elsewhere, in this case, people feel such a situation very unfair. Revolted by their current situation, they organized in an NGO fighting for the rights. As credit-debt-slavery is broadening the social base for resistance, we need to ask: how should we define these forms of resistance? Are they new forms of rights-oriented movements defending civil rights and equality before the law (for example, the right for a housing or social/financial security)? Or can we truly speak of a new kind of middle-class resistance, focused on the rising inequalities produced by the present economic order, as articulated by the 99% slogan?